Validity of the Metacognitive Awareness Instrument for Prospective Mathematics Teacher Students - Nita Hidayati; Y.L. Sukestiyarno; Emi Pujiastuti; Sugiman Sugiman; Wardono Wardono (Universitas Negeri Semarang, 2026)
The purpose of this study is to describe the validity of the metacognitive awareness instrument which includes metacognitive knowledge and regulation. The metacognitive awareness instrument is in the form of a questionnaire consisting of 52 statements. This study is a qualitative descriptive study to assess and obtain the quality of a valid metacognitive awareness instrument to characterize students' metacognitive awareness. The student metacognitive awareness instrument was validated by two psychologists and a linguist. The metacognitive awareness instrument was also empirically validated by involving 28 mathematics education students as respondents. The results of the study show: (1) the validator's assessment of the metacognitive awareness instrument from the aspect of content validity is categorized as valid and reliable (Cohen's kappa = 0.29), (2) the metacognitive awareness instrument is empirically valid (Pearson Correlation > r table) and reliable (Cronbach's alpha = 0.754). These results indicate that the metacognitive awareness instrument can be used to characterize the metacognitive awareness of prospective mathematics teacher students.